English: Indonesia - Ika Agustina; Indri Astuti Handayani; Guritno Syahputra (Jurusan Farmasi, Politeknik Kesehatan Kementerian Kesehatan Aceh, 2026)
Nutmeg shell waste in Indonesia can be processed into activated charcoal for cosmetic products. However, its formulation into liquid soap presents a technical constraint, as viscous surfactants risk coating the charcoal pores, thereby reducing adsorption capacity. This study aimed to formulate a liquid bath soap using nutmeg shell activated charcoal and evaluate its physical quality and adsorption capacity. The charcoal was prepared through thermal processing at 300°C and 500°C. This process yielded charcoal with a low ash content (2.68%) and a high iodine adsorption capacity (989.82 mg/g). The charcoal was subsequently incorporated into a liquid soap base at concentrations of 0% (Base), 5% (F1), and 10% (F2). The evaluation showed that the pH values of the soap (8.19–8.25) complied with the SNI 4085:2017 standard. Although the viscosity (5,680–6,400 mPas) remained above the maximum limit, the addition of charcoal significantly reduced the viscosity (p < 0.05). Furthermore, the adsorption capacity of the soap increased with higher charcoal concentrations (p < 0.05), reaching 380.67 mg/g for F1 and 609.14 mg/g for F2. In conclusion, the pores of the nutmeg shell activated charcoal remain open and functional within the liquid soap formulation, demonstrating its effectiveness as a deep-cleansing agent.